2017
DOI: 10.14295/ras.v31i1.28548
|View full text |Cite
|
Sign up to set email alerts
|

Interação rio-aquífero e a meiofauna do ambiente hiporreico

Abstract: Resumo -As interações que ocorrem entre a água superficial (rios e lagos) e água subterrânea envolvem uma série de processos que devem ser explorados no intuito de entender suas interligações, já que a taxa de recarga e a qualidade da água subterrânea dependem fortemente das características dessa interface. A zona de intercâmbio, conhecida por zona hiporreica é formada por uma camada subsuperficial de sedimentos entre o leito do rio e o aquífero, e suas características favorecem o estabelecimento de algumas es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
1
2
Order By: Relevance
“…Regarding the meiofauna analysis, contrary to the reports of M. A. Palmer (1990), Veras, da Silva Pereira Cabral, de Paiva, and Barreto (2017); Veras et al (2018) who found a great abundance of rotifers in freshwater ecosystems, our research identified a low abundance of the Rotifera group (2% of the total sampling). This difference becomes more significant regarding the studies of Veras et al (2017Veras et al ( , 2018, because they were made also in Beberibe River, but their sample collections were made more than two years before the collections made in this research, indicating that there was a change in the structure of meiofauna community.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the meiofauna analysis, contrary to the reports of M. A. Palmer (1990), Veras, da Silva Pereira Cabral, de Paiva, and Barreto (2017); Veras et al (2018) who found a great abundance of rotifers in freshwater ecosystems, our research identified a low abundance of the Rotifera group (2% of the total sampling). This difference becomes more significant regarding the studies of Veras et al (2017Veras et al ( , 2018, because they were made also in Beberibe River, but their sample collections were made more than two years before the collections made in this research, indicating that there was a change in the structure of meiofauna community.…”
Section: Discussioncontrasting
confidence: 99%
“…O fluxo de água que ocorre devido à interação rio-aquífero na zona hiporreica favorece o estabelecimento de organismos, pois existe uma grande infiltração de matéria orgânica nos interstícios dos sedimentos (VERAS et al, 2017). Entre os diversos grupos de organismos que possuem o ambiente hiporreico como habitat, destaca-se a meiofauna.…”
unclassified
“…No qual, mudanças globais podem gerar efeitos negativos, principalmente para a cadeia alimentar bentônica; e podem favorecer algumas espécies meiofau-nísticas, uma vez que podem exibir notáveis adaptações fisiológicas (GIERE, 2009;MARIA;WANDENESS;ESTEVES,2016). Veras (2017) reitera que os ciclos de vida de pequena duração dos seres da meiofauna, que vão de 1 a 3 meses, facilitam nas observações em estudos de curto prazo.…”
unclassified
“…BF consists of the indirect abstraction of water from a surface source with pumping wells close to the river (or lake), causing an increase in the difference of hydraulic head between the source and the water table, which induces the passage of water through the porous medium to the well (RAY, 2002). In this technique, physical, chemical, and biological processes occur (FREITAS et al, 2018), mainly during the passage of water through the Hyporheic Zone (HZ), which is the transition zone between the surface environment and the underground environment (VERAS et al, 2017). The HZ plays a fundamental role in the river-aquifer interaction, acting as a regulator in the water flow and as a natural filter (MUG-NAI; MESSANA; DI LORENZO, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentological characteristics of the HZ are important for directly determining the spatial and structural conditions and indirectly determining the physical and chemical environment of the sediment (MUGNAI; MESSANA; DI LORENZO, 2015). In addition, meiofauna is important to influence the spatio-temporal distribution of the hyporheic meiofauna (VERAS et al, 2017).…”
Section: Introductionmentioning
confidence: 99%